Putting Organizational Studies in Indonesia into The Right Track: Dialectic between Positivism and Interpretivism - Arif Hartono (Jurnal Siasat Bisnis, 2008)
Positivism-quantitative has been well known many years as research mainstream on organizational studies in Indonesia. However, the implementation of positivism-quantitative approaches was not utilized appropriately. It is reasonable because these approaches were born in western society and culture, which is so difference with Indonesian one. Based on this argument, the implementation of interpretive-constructive-qualitative approaches for exploring and investigating Indonesian cases would be better since it is more appropriate for Indonesian organizational life.Keywords: positivism, interpretivism, social differences, cultural differences, Indonesian model